Walkability factors for a campus street - Harun, Nor Zalina; Nashar, Amanina; Bachok, Syahriah (Malaysian Institute Of Planners, 2020)
It has been reported that translating walkability is complicated, particularly the execution of its theory in planning practices. This study untangled the queries by presenting factors that makes campus interesting, walkable. and more importantly to be characterised as 'pedestrian friendly campus'. For this purpose, campus street walkability factors were analysed using factor analysis to find out the most significant measures of street walkability in the campus and its underlying items. All data has been run through SPSS beforehand and have met the assumption required for factor analysis that were formulated with the sample size of 500 respondents. The result from the study reveals that walkability factors of the campus were gratified from four significant factors that are classified as comfort-connectivity, safety and accessibility. The study reveals that proper streetscape design uncovers various potentials of the streets in forming part of a successful campus open space in the future. Moreover, the empirical findings in this research have provided a new understanding of the street function. Aside from functioning as space connectors, the streets offer broader opportunities for various pedestrian activities, which consists of passive and active activities that would contribute to the students' social and physical enhancement.